2021
DOI: 10.3390/separations8120227
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD Analysis of Hemp Oil Supplements for Determination of Four Cannabinoids: Cannabidiol, Cannabidiolic Acid, Cannabinol and Delta 9-Tetrahydrocannabinol

Abstract: Growing consumer interest in hemp oilseed supplements requires quality control. Therefore, appropriate, effective and verified analytical methods are needed for the determination of some bioactive cannabinoids in them. The aim of the study is to present an extended (compared to our previous research) validated high performance liquid chromatography with diode array detection (HPLC-DAD) method for the determination of four cannabinoids (cannabidiol, cannabidiolic acid, cannabinol and delta-9-tetrahydrocannabino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Therefore, their results confirmed the classification of the studied samples as fiber [ 54 ]. In order to grow consumer interest in hemp oilseed supplements, four main cannabinoids of CBD, CBDA, CBN, and ∆-9-THC in an oil matrix of seven commercial hemp oil supplements have been determined [ 55 ]. They reported that the cannabinoid composition is required to be monitored in such supplements, as in some cases, the cannabinoids concentration in analyzed samples differed significantly from those declared by the manufacturers [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, their results confirmed the classification of the studied samples as fiber [ 54 ]. In order to grow consumer interest in hemp oilseed supplements, four main cannabinoids of CBD, CBDA, CBN, and ∆-9-THC in an oil matrix of seven commercial hemp oil supplements have been determined [ 55 ]. They reported that the cannabinoid composition is required to be monitored in such supplements, as in some cases, the cannabinoids concentration in analyzed samples differed significantly from those declared by the manufacturers [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of the pharmacology of these compounds and the knowledge of their beneficial effects in the treatment of pain, post-chemotherapy emesis, neuropsychiatric conditions, and dermatological conditions, in particular, stimulated researchers to address topics related to optimal formulations. Theoretically, the most promising formulations, which exceed the limitations imposed by the physico-chemical characteristics of cannabinoids, mentioned above are those that allow their administration on the skin [ 154 ]. Among these skin administration methods, we focus on those based on nanotechnology, that have, as observed in Figure 4 , better penetration through skin layers than conventional formulations.…”
Section: The Topical Versus the Transdermal Route Of Administration F...mentioning
confidence: 99%
“…These difficulties not only led to the use of permeability enhancers such as oleic acid and ethanol but also techniques that modify the characteristics of the molecule by using microemulsions, physical amplifiers (microneedles and electroporation), iontophoresis, ultrasound, magnetophoresis, encapsulation in micro-/nanogels, nanoparticles, and nanocarriers [25,73,76]. Cannabidiolic acid (CBDA) 4.86 [154] Cannabidiol (CBD) 5.79 [155] Cannabinodiol (CBND) 6.00 [156] Δ9-trans-tetrahidrocannabinol (THC) 7.26 [157] Δ8-trans-tetrahidrocannabinol (Δ8-THC) 7.4 [156] Cannabigerol (CBG) 7.47 [158] Cannabidiol (CBD) 5.79 [155] Pharmaceuticals 2023, 16, x FOR PEER REVIEW 16 of 35…”
Section: The Skin As a Potential Route For Systemic Administrationmentioning
confidence: 99%
See 2 more Smart Citations